Penerapan dan Pelatihan Penggunaan Semesta untuk Pelaksanaan Tugas Akhir di Fakultas Pertanian Universitas Panca Bhakti - Siswanto, Lindung; Rolansa, Freska; Bibi, Sarah; Suryanto, Tommi; Budianingsih, Budianingsih; Faisal, Ferry; Wibowo, Fitri; Tharam, Medi Yuwono; Hermanto, Bangbang (Kapuas, 2023)
One form of service provided, especially in institutions engaged in education, is the service process in the implementation of the Final Project/Thesis where the implementation process itself is currently still being done manually which makes the entire implementation process take longer and less efficient, as well as the distribution conditions. Covid-19 (corona virus) which is currently still not showing a decline until the Government issues government regulations, circulars and appeals for the implementation of face-to-face activities to be reduced and shifted to online / online. This information system is the result of research that has been implemented in the Department of Electrical Engineering, Pontianak State Polytechnic, named SEMESTA which is an acronym for Information System for Final Project Completion. Which has three user entities, namely students, supervisors and administrators. The information system is able to serve title proposals, proposals, submission of supervisors, selection of students to be mentored, and consultation media between students and their supervisors for the smooth process of online and real-time final assignments/thesis. Faculty of Agriculture, Panca Bhakti University, Pontianak currently does not have an information system that can be used to help complete the final project/thesis. If this information system is implemented then the parties who will be involved in this information system will be trained how to use it separately based on the level of users.